WAY TO PLAY WITH MUSICAL INSTRUMENT IN HIGH SKILL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This national article highlights important aspects of performing arts, providing guidance for the performer on the results of one-on-one training. At the same time, scholars comments are cited.